EVALUASI KONDISI LINGKUNGAN KERJA PADA BAGIAN PROSES PENGECORAN DI INDUSTRI KERAJINAN COR ALUMUNIUM PT âEDâ YOGJAKARTA - Oesman, Titin Isna (Industrial and Systems Engineering Assessment Journal (INASEA), 2014)
The process of industrial production in cast aluminum craft PT "ED" is done manually and begins the process of smelting aluminum with temperature (650-700) Â° C and continued the process of pouring the mold over and over again (repetitive). This condition can cause heat stress and have health impacts for operators due to heat exposure if not properly managed. The purpose of this study is to determine the condition of the working environment in the process of casting in cast aluminum craft industry "ED" Yogjakarta. The study is conducted in the process of aluminum casting and foundry "ED" in Yogjakarta. The sample in this study is the operators on the production process of aluminum casting and pouring in aluminum craft industry "ED" Jogjakarta which amounted to 12 people. Measuring instruments used in this study are as follows. Camera, Stop watch, WBGT-meter, Luxmeter, Bathroom scale and Digital Sound level meter. Data subject conditions and environmental conditions is obtained and analyzed descriptively.